"Since when have people been illegal?": Latinx youth reflections in Nepantla. Issue 4 (December 2018) - González Ybarra, Mónica
Abstract Using Gloria Anzaldúa's idea ofnepantla alongside critical theories of race and citizenship, this article highlights how Latinx undocumented youth and youth of mixed status families navigate, resist, and at times endorse the various and competing discourses around immigration, citizenship, and illegality. The author uses pláticas as a methodological and pedagogical tool with youth who live in a migrant housing complex to examine how they enter sociopolitical conversations centered on their lived realities. Drawing on the youths' reflections, the author emphasizes a need to centralize and create spaces for the voices of youth within discussions and action around immigration and citizenship, because they are continuously subjected to and forced to navigate dominant narratives and discourses that surface about them, their families, and (im)migrant communities.